Estrategias reproductivas de las lagartijas brasileñas del género Tropidurus rodrigues, 1987 (Squamata, Tropiduridae) en lo temporal y espacial - Ferreira, Adelina; Kihara, Virginia Ojeda; Mehanna, Mahmoud [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
SUMMARY: Reproductive strategy is the set of adaptations that promote the most efficient way that the species will survive under the particular conditions of a determined environment. Understanding these adaptations is important and can help pinpoint populations indicator of environmental changes. Spermatogenesis is a measurable biological process of these adaptations in spatial and temporal scales. We analyzed the morphology of the testes and oviducts of the lizard species that comprise the genus Tropidurus, taking into account the geographical distribution and sympatric relations. For the analysis and the testes were removed from the middle part of the oviducts from Tropidurus etheridge, T. oreadicus, T. itambere, T. spinulosus and T. Guarani species, collected in different places in the Mato Grosso state, Brazil. The reproductive period is synchronous for males and females and occurs in September, October and November. Reproductive males were characterized. In the testes are seminiferous tubules with germ cells at different stages of spermatogenesis, with a high epithelium, at present light, free spermatozoa in the lumen and reduction of interstitial tissue. For females, the reproduction peak occurs when the oviduct epithelium is high with secretions and basal nucleus. These months are characterized in the sampled areas over a period of heavy rain and high temperatures. The decline of reproductive period was observed in both sexes, between April and August. Low reproduction in males is characterized by ample light, absence of sperm, only germ cells in the early stages of spermatogenesis are observed (a few spermatogonia and spermatocytes) and interstitial tissue wide. In females, the period of reproductive decline is marked by the absence of unicellular glands in the oviduct epithelium, with higher affinity with the dye. This period corresponds to low rainfall periods and lower temperatures. We propose an analysis of zoological samples; this is a proposal to facilitate the work of many researchers through access to the species, especially rare species.
Reproductive strategies of Brazilian lizards of the genus Tropidurus rodrigues, 1987 (Squamata, Tropiduridae) in the temporal and spatial
Keywords: Brazil; Lizards; Reproductive cycle